2020
DOI: 10.1021/acs.macromol.9b02057
|View full text |Cite
|
Sign up to set email alerts
|

Light Scattering Study of Internal Motions of Ultralong Comb-like Chains in Dilute Solutions under Good Solvent Conditions

Abstract: Internal dynamics of polymer chains is one of the most important fundamental problems in polymer physics. This work reports the first example of a dynamic light scattering (DLS) study of internal motions of well-defined ultralong comb-like chains in dilute solutions under good solvent conditions. Using two well-characterized comb-like model samples with controlled parameters and narrow distributions (M w /M n ≈ 1.30 and M w ≈ 10 7 g/mol), the asymptotic behavior of the reduced first cumulant [Γ* = Γ(q)/(q 3 k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
1
7
1
Order By: Relevance
“…As shown in Figure , the average sizes are found to increase with the grafting density but irrelevant with the chain topology. For both l -PPA- g -PS 23 and c -PPA- g -PS 23 , ellipsoidal and spherical morphologies are observed, which is different from our previously observed wormlike chain morphology for l -PPA 19000 - g -PS 13 with an ultralarge DP of the backbone . In addition, the morphology of cyclic graft polymers is also different from that reported by Schappacher and Deffieux .…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…As shown in Figure , the average sizes are found to increase with the grafting density but irrelevant with the chain topology. For both l -PPA- g -PS 23 and c -PPA- g -PS 23 , ellipsoidal and spherical morphologies are observed, which is different from our previously observed wormlike chain morphology for l -PPA 19000 - g -PS 13 with an ultralarge DP of the backbone . In addition, the morphology of cyclic graft polymers is also different from that reported by Schappacher and Deffieux .…”
Section: Resultscontrasting
confidence: 96%
“…The modifications of linear and cyclic backbones with propargyl bromide were conducted with a tetramethylguanidine promoted esterification approach according to the literature, which furnished the alkyne-functional l -PPA and c -PPA, respectively. As shown in Figure a, the SEC curves of l -PPA and c -PPA still show the difference in M p,c / M p,l , which is found to be around 0.80 (Table ), similar to that for P t BA samples. In addition, the observed characteristic peak “h” in Figure b, attributed to the proton signal from the alkyne group, also indicates the success of esterification.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Comblike polymers have an intrinsic ability toward forming ordered structures, and understanding the structure of comb polymers is a pre-requisite to controlling their performance. There are also some reports on the regulation of mechanical properties by tuning the structural parameters of comblike macromolecules. Urban et al have demonstrated that simple comb polymers based on methyl methacrylate and n -butyl acrylate show repeatable self-healing properties, which rely on van der Waals interactions and have significant implications for the fabrication of low-cost self-healing polymers and coatings. The present study focuses on coarse-grained MD (CGMD) simulations of alternating comblike molecules with a goal to fundamentally probe the influence of different kinds of architectural parameters on the mechanical and self-healing properties of such materials.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer Chemistry different from our previously observed wormlike chain morphology for PPA 19000 -g-PS 13 with an ultralarge DP of the backbone. 24 In the sample preparation process before the AFM measurements, the dilute polymer solution shows a strong concentration during the solvent evaporation process and the alkane side chain itself is crystalline, so we believe that the chain dynamics can affect the conformational state, aggregation state, and the resulting morphology.…”
Section: Papermentioning
confidence: 99%